When the Tail Counts: The Advantage of Bilingualism Through the Ex-Gaussian Distribution Analysis - Calabria, Marco; Hernandez, Mireia; Martin, Clara D.; Costa, Albert (Frontiers in Psychology, 2011)
Several studies have documented the advantage of bilingualism with respect to the development of the executive control (EC) system. Two effects of bilingualism have been described in conflict resolution tasks: a) bilinguals tend to perform the tasks faster overall, and b) bilinguals tend to experience less interference from conflicting information, compared to monolinguals. The precise way in which the bilingual advantage relies on different EC mechanisms is still not well understood. The goal of the present article is to further explore how bilingualism impacts the EC system by performing a new analysis (Ex-Gaussian) of already reported data in which bilinguals and monolinguals performed a flanker task. Ex-Gaussian distribution analysis allows us to partial out the contribution of the normal and the exponential components of the RT distribution of the two groups. The fit of the raw data to the ex-Gaussian distribution showed two main results. First, we found that the bilingualism advantage in the overall speed of processing was captured by group differences in the normal (μ) and the exponential (τ) components of the distribution. Second, the bilingual advantage in the magnitude of the conflict effect was captured by group differences only in the exponential component. The results are discussed in terms of: a) usefulness of the ex-Gaussian analysis as a tool to better describe the RT distribution, and b) a new approach to explore the cognitive processes purportedly involved in instantiating the bilingualism advantage with respect to EC.